Polymorphisms of estrogen metabolism-related genes ESR1, UGT2B17, and UGT1A1 are not associated with osteoporosis in artificial menopausal Japanese women - Yokota, Megumi; Hirasawa, Akira; Makita, Kazuya; Akahane, Tomoko; Sakai, Kensuke; Makabe, Takeshi; Horiba, Yuko; Yamagami, Wataru; Ogawa, Mariko; Iwata, Takashi; Yanamoto, Shigehisa; Deshimaru, Ryota; et al. (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Bilateral salpingo-oophorectomy (BSO) is a risk factor for osteoporosis. Previous studies have reported an association between genetic polymorphisms and the risk of developing osteoporosis. However, the relationship between osteoporosis and genetic polymorphisms in Japanese women treated with BSO is not well understood. To improve the quality of life for post-BSO patients, it is important to determine the genetic factors that influence their risk for osteoporosis. The aim of this study was to investigate the association between gene variations of estrogen metabolism-related genes and osteoporosis in surgically menopausal patients, which may improve the quality of life for surgically menopausal patients. Material and methods : This study included 203 menopausal women treated with BSO because of gynecologic disorders. One hundred and twenty-six women with artificial (surgical) menopause, who had undergone BSO in the premenopausal period, were compared with 77 women with natural menopause, who had undergone BSO in the postmenopausal period. The women were tested for bone mineral density to diagnose osteoporosis. Polymorphisms of estrogen receptor 1 ( ESR1 ) and UDP-glucuronosyl transferase (UGT) genes UGT2B17 and UGT1A1 were analyzed, and their association with bone mass and osteoporosis was statistically evaluated. Results : No significant association was found between osteoporosis and polymorphisms in ESR1 , UGT2B17 , or UGT1A1 in both groups, suggesting that BSO might be a more significant physiological factor in influencing bone mass density compared to genetic variations. Conclusions : These results suggest that the ESR1 , UGT2B17 , and UGT1A1 polymorphisms are not genetic factors affecting osteoporosis in postmenopausal Japanese women.